A FISIOTERAPIA NO DESMAME DA VENTILAÇÃO MECÂNICA: RELATO DE CASO - Klahr2, Patrícia d. S.; Coracini, Maria A.; Windmöller, Pollyana; Souza, Regina M. H. d.; Eickhof, Cheila M. (Salão do Conhecimento, 2013)
Resumo